The Contribution of Corporate Social Responsibility for Increasing Corporate Image and Word of Mouth in Indonesia Islamic Bank - Suryani, Tatik; Lindiawati, Suhartono (Journal of Entrepreneurship, Business and Economics; Vol 6 No 2 (2018), 2018)
Recently Corporate Social Responsibility (CSR) is highlighted as an important factor to make figure in many industries. Interestingly, there are not many researches in Islamic banking industry. The purpose of this research is to analyze whether CSR has a significant relationship toward Corporate Image (CI) and Word of Mouth (WOM) in Islamic bank. Furthermore, this research also to examine the effect of CI toward WOM in Islamic banking industry. The data is collected using questionnaire method involving 238 bank’s customer who get chosen for CSR program from bank. The data is analyzed using Partial Least Square. The result from this research showed that CSR has a positive significance effect towards CI and CI has positive has positive significant effect towards Word of Mouth. In the end, this research revealed that banking industry should focus more on implementing effective CSR because it shows positive correlation toward creating positive CI and WOM which could persuade customer decision toward choosing their personal Bank. Research paper Keywords: CSR, Corporate Image, WOM Reference to this paper should be made as follows: Suryani, T., & Lindiawati, S. (2018). The Contribution of Corporate Social Responsibility for Increasing Corporate Image and Word of Mouth in Indonesia Islamic Bank, Journal of Entrepreneurship, Business and Economics , 6 (2), 29–44.